Experimental and finite element studies on the flexural behavior of optimized green concrete using GGBS and pond ash. (2022) - Naga Theera Hari, M.; Ragul, P.; Chellapandian, M.; Vincent, P.
Abstract: In this paper, the flexural behavior of reinforced concrete (RC) beams developed using an optimized green concrete with pond ash (PA) and ground granulated blast furnace slag (GGBS) as a partial replacement for river sand and cement was studied. In total, 16 mixes were prepared by replacing cement using GGBS up to 50% and river sand by pond ash up to 30% in tandem. From the different mixes cast, an optimized green concrete mix with GGBS and pond ash was selected based on the performance of fresh (slump test) and hardened properties (compressive strength). The optimized mix with 30% GGBS and 20% pond ash was used further for understanding the flexural behavior of RC beams. In specific to this study, six RC beams were tested by varying shear span (a) to depth (d) ratios. In addition to the experimental study, a detailed three dimensional finite element analysis (FEA) was performed using the ABAQUS software and validated with the test results.